Acute coordinative exercise ameliorates general and food-cue related cognitive function in obese adolescents. Issue 8 (17th April 2020) - Zhang, Ligong; Chu, Chien-Heng; Liu, Jen-Hao; Chen, Feng-Tzu; Nien, Jui-Ti; Zhou, Chenglin; Chang, Yu-Kai
ABSTRACT: Whether the acute coordinative exercise could affect the inhibitory control and food-cue related attention in obese adolescents remains understudied. Therefore, this study used the Stroop test and the food-cue related Stroop test to explore the impacts of 20 min of acute coordinative exercise on the cognitive tests involving inhibitory control and attentional bias towards food-cue related stimuli, respectively, in obese adolescents. Thirty-eight obese adolescents (mean age = 14.63 ± 0.69 years) were equally divided into exercise and control groups. The cognitive tests (i.e., the Stroop test and the food-cue related Stroop test) and hunger scores were conducted and assessed before and after an intervention. The exercise group had significantly larger negative pre-post response time difference in the congruent (−1.04 ± 0.29 ms) and incongruent (−5.76 ± 1.66 ms) conditions of the Stroop test than the control group ( p s < 0.01), and a smaller post-interference (1.13 ± 0.14) than the pre-interference (1.31 ± 0.14, p = 0.04). Moreover, a significantly larger negative pre-post response time difference on the food-cue related Stroop test was observed in the exercise group (−4.42 ± 7.20 ms) than the control group (1.76 ± 8.37 ms, p = 0.02). Collectively, an acute coordinative exercise session could induce superior inhibitory control and less attentional bias towards food-cue related stimuli in obese adolescents.